Jenuh Belajar: Strategi Orang Tua dalam Membersamai Anak Belajar di Masa Pandemi COVID-19 - Fauziah, Nurul; Nadlifah, Nadlifah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2021)
The COVID-19 pandemic has changed the implementation of learning in early childhood. Monotonous learning is the focus of this research problem. The purpose of this study is to analyze how the strategies adopted by parents in dealing with children who are bored with learning during the COVID-19 pandemic and the factors that influence it. This type of research is descriptive qualitative research. The research location is in TK Masyithoh II Sanansari. The research subjects were principals, teachers, parents, and students. Collecting data using observation, interviews, and documentation. Data analysis was carried out using the Milles and Huberman model, namely data reduction, display data, and conclusion drawing/verification data. Test the validity of the data using source triangulation and technical triangulation. The results of the study showed that the learning saturation of Group B TK Masyithoh II Sanansari Kindergarten during the COVID-19 pandemic was because students did not have friends to exchange imagination and learning was monotonous. The strategies used by parents are: repeating orders, providing psychological support for children, and providing rewards. The supporting factors, namely: intrapersonal encouragement and encouragement from the family. While the inhibiting factors consist of: unstable child's mood, busy family, and the surrounding environment. The findings of this study have an educational impact on parents in accompanying children to learn during the COVID-19 pandemic and recommend parents to use this strategy as well as evaluation materials for early childhood educators.